Design and Analysis of Contingent Valuation Surveys Using the Nested Tobit Model - Howe, Charles W.; Lee, Byung-Joo; Bennett, Lynne L. (The Review of Economics and Statistics, 1994)
Charles W. Howe, Byung-Joo Lee, Lynne L. Bennett, Design and Analysis of Contingent Valuation Surveys Using the Nested Tobit Model, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 385-389